A tradição discursiva e a gramática do design visual no anúncio publicitário - Bonifácio, Carla Alecsandra de Melo (2011)
From the publicity texts, which are presented in several supports both in printing and electronic press, the aim of this work is describe the change and permanence traces in the composition of the advertising Discoursive tradition mainly, those of products to the female public, which circulated in Brazil in the magazine O Cruzeiro from the twentieth century (1950-1965), comparing them with the advertisings published by the magazine Claudia in the first decade of the twenty-first century (2000-2010). In order to achieve this aim, it was used: the theoretical framework of the Discoursive traditions that takes into consideration the relation a text can have with another one and the degree of repetition, not being a simple linguistic reproduction, but the discoursive use of the language in a concrete situation; Bakhtin`s transformation/ transmutation proposal (2003) of the discoursive gender, which studies the gender as a set relatively stable of conventions that are connected to social accepted activities, as well as the studies developed about the Grammar of Visual Design by Kress and Theo van Leeuwen (2000) to the analysis of the elements related to the non verbal language. Taking into consideration that the genders are changeable, once they are result of social practices reflecting into the language, it is justified the importance of this research due to the essential role the press has developed in the society from the nineteenth century to the present. The analysis revealed that although the advertising discoursive tradition has kept in its composition structure elements that allow its recognition as advertisements, as the name of the product and the trend, this gender has passed through an intern innovating transmutation, once the recognized changes occur inside the gender without incorporating other.